Literature Review: Benefits of Balloon Blowing Breathing Exercises on Lung function in Astma Patients - DWI NINGSIH, ARUM (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Chronic inflammation that occurs in asthmatic patients results in recurrent episodic symptoms such as shortness of breath, chest tightness, coughing, and wheezing breath sounds. This indicates that there is impaired lung function which can be seen from the results of the Peak Expiratory Flow (APE) examination. The purpose of compiling a literature review is to analyze the benefits of breathing exercise therapy using the balloon blowing technique on lung function in asthma patients. The method used in this literature study is the PICOS framework. Article searches were carried out using the science database from Science Direct, Pub Med and Google Scholar. The keywords used are breathing exercises, Balloon Blowing and asthma or asthma. Results have been literature found 7 articles analyzed. A total of 5 articles discussed the effect of breathing exercises using the balloon blowing technique on lung function, namely in terms of Peak Expiratory Flow (APE) values ​​and 2 journals discussed the effect of balloon blowing on improving clinical symptoms, namely shortness of breath and increased oxygen saturation. Based on the results of the literature review, it can be concluded that the Balloon Blowing breathing exercise can be applied to asthma patients. This exercise, when performed according to correct and regular procedures, can improve lung function which can be seen from several indicators, namely increasing Peak Expiratory Flow (APE), oxygen saturation and decreasing complaints of shortness of breath.